Helicobacter pylori and histopathological findings in patients with dyspepsia - Cansel TÜRKAY,; Mustafa ERBAYRAK,; Nükhet BAVBEK,; Sibel YENİDÜNYA,; Elife ERASLAN,; Benan KASAPOĞLU, (Turkish Journal of Gastroenterology, 2019)
-